2009
DOI: 10.1111/j.1745-9125.2009.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Delinquency Balance: Revisiting Peer Influence*

Abstract: An impressive number of inquiries across an array of methodological specifications has demonstrated that deviant peers are an important correlate of various criminological outcomes, which include within‐ individual change and stability in offending behavior. Still, the causal mechanisms of peer influence arguably remain underdeveloped (Giordano, 2003; Warr, 2002). In an attempt to expand the dialogue on the nature of peer influence, this inquiry proposes that scholars would benefit from considering relative pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 85 publications
(103 reference statements)
5
102
0
Order By: Relevance
“…This is a pertinent avenue to explore as studies on youth behavior have consistently found that perceptions of peers' behaviors and attitudes have great capacity to influence youths' actions (Perkins 2002(Perkins , 2012Perkins and Berkowitz 1986). Indeed, studies on the impact of the behavior of delinquent peers on one's own behavior consistently suggest a strong correlation between reports of friends' actions and self-reported behavior (see McGloin 2009;Warr and Stafford 1991). It stands to reason that bullying behavior may follow similar conventions.…”
Section: The Role Of Perceptionsmentioning
confidence: 86%
“…This is a pertinent avenue to explore as studies on youth behavior have consistently found that perceptions of peers' behaviors and attitudes have great capacity to influence youths' actions (Perkins 2002(Perkins , 2012Perkins and Berkowitz 1986). Indeed, studies on the impact of the behavior of delinquent peers on one's own behavior consistently suggest a strong correlation between reports of friends' actions and self-reported behavior (see McGloin 2009;Warr and Stafford 1991). It stands to reason that bullying behavior may follow similar conventions.…”
Section: The Role Of Perceptionsmentioning
confidence: 86%
“…This knowledge has moved researchers away from debating whether peers play a role in explaining behavior and toward understanding the conditions under which peer influence operates. For example, scholars have examined the validity of different measures of peer delinquency (see McGloin, 2009) and utilized social network data to encapsulate the peer effect (see Haynie, 2001). Unstructured socializing is yet another manifestation of the peer effect that prior work has linked to general delinquency, substance use, and dangerous driving (see Haynie & Osgood, 2005;Osgood & Anderson, 2004;Osgood et al, 1996).…”
Section: Implications For Theory Research and Policymentioning
confidence: 99%
“…On the other hand, theories on social learning and peer effects point to lower re-offending rates among offenders serving with EM with reference to the interactions with other criminals, the training of criminogenic skills and the hardening of offenders in prison. Within this framework, exposure to deviant peers is assumed to prompt higher levels of delinquency due to deviant attitudes and norms, direct modeling and indirect reinforcing effects (see e.g., Akers 1998;Mcgloin 2009). Empirical studies have documented causal peer effects and specialization among inmates (e.g.…”
Section: Introductionmentioning
confidence: 99%